Delphi method proposed in public policy innovation [Propuesta de método delphi en políticas públicas de innovación] (2015)
This article presents a proposal and prioritization analysis of innovation public policies through the application of the Delphi method. The fundamental purpose is to bring elements to answer the following question: ¿Do good innovation policy practices exist in Colombia? To contribute to this survey, an anonymous Delphi consultation method was made to experts with 92 variables in two rounds; which was sent to representatives of universities, Government enterprises, and Colombian interface entities. This is done with the purpose of prioritizing innovation policies of Colombia for the year 2025. The document is divided in various sections. A revision is presented on the concepts of innovation policies. Later, a revision is made regarding innovation public policies of the Asian Tigers and some countries of OECD, just like an analysis of the legal innovation framework in Colombia. The study ends with the application of the Delphi method on innovation public policies in Colombia for the year 2025.